Evaluation of the Clinical Safety of the Low‐Cost Warburg Therapy for the Treatment of Patients With Advanced Cancers - Peihua Lu; Tom Tsang; Michael S. Badowski; Michael E. Pennington; Linda C. Meade‐Tollin (Cancer Medicine)
ABSTRACT Background Rising cancer care costs are becoming cost prohibitive for lower income people worldwide. We developed the Warburg protocol as a low‐cost option for the treatment of cancer that was inspired. It was developed to exploit an Achilles heel which is a hallmark of cancer cells; the metabolic requirement for higher levels of glucose than normal cells. Objective The purpose of this report is to assess the clinical safety and affordability of the Warburg therapy as an option for patients with advanced cancers. Methods Between 2021 and 2023, 251 patients with advanced cancers received a total of 8542 treatments with the Warburg therapy. To restrict the supply of blood glucose to cancerous tumors, regular human insulin was administered (IV) sufficient to reduce blood glucose concentrations to hypoglycemic levels for 40–60 min. Subroutine doses of fluorouracil and cyclophosphamide were administered intravenously during this hypoglycemic period. Food or intravenous glucose was given as needed to return blood glucose to euglycemic levels after treatment. Patient symptoms, status, vitals, blood glucose, and hypoglycemic symptoms were monitored throughout treatment. Various blood parameters were measured before and after patients' course of treatment. Results There were no irreversible adverse reactions in advanced tumor patients of different ages and different cancer types after treatment. There was no significant fluctuation in blood glucose levels in diabetic and non‐diabetic patients after treatment, and the weight, vital index and blood biochemical index of patients before and after multiple treatments exhibited little variation. Conclusion Warburg therapy for the treatment of advanced tumors is clinically feasible, and safe for multiple treatments. It is inexpensive and widely applicable to different patient groups.